The Influence of Job Training and Career Development on Employee Performance at PT. Bank Sumut Imam Bonjol Branch - Arnida, Yuli; Syahputra Amri; Nanda Fitria Aulanda (Smart International Management Journal, 2024)
The aim of this research is to determine and analyze the influence of job training and career development on employee performance at PT Bank Sumut Imam Bonjol Branch, both partially and simultaneously. The approach taken in this research is an associative approach. This research uses primary data where data is collected using a questionnaire and uses secondary data originating from books and previous research journals. The population in this study were employees of the general division of PT Bank Sumut Imam Bonjol Branch, namely 35 people and the total sample was 35 respondents. The data collection technique uses a questionnaire. The data analysis technique in this research uses SPSS 25. The results of data analysis show that job training has no significant effect on employee performance and career development has no significant effect on employee performance. And in terms of variables, discipline, job training and career development have a significant effect on employee performance.